MEDICAMENTOS BIOSSIMILARES DE ANTICORPOS MONOCLONAIS NO TRATAMENTO DE TUMORES SÓLIDOS - Armando Alcobia; Jorge Espírito Santo; José Aranda da Silva; Florbela Braga; Helena Gervásio; Joaquim Abreu de Sousa; João Gonçalves; Clementina Varela; Noémia Afonso (Formifarma, LDA., 2015)
.